Investigating macro factors affecting the technological innovation system (TIS): A case study of Iran's photovoltaic TIS - Mohammad Esmailzadeh (Energy Strategy Reviews, 2020)
Innovation systems operate in specific regional, political, social and economic contexts and are influenced by their environment. The internal structures and processes of a technological innovation system (TIS) are usually well understood in the literature, but what is happening outside and across the boundaries of the system is less systematically considered. This paper tries to fill this gap by combining the TIS concept and multi-level perspective (MLP) in studying problems impeding the development of photovoltaic technology in Iran. Considering MLP, this paper firstly identifies the most influential macro factors on photovoltaics TIS by studying the literature and semi-structured interviews. Then, the relationships between these factors were explained using the Interpretive Structural Modeling (ISM) technique. We used cross-impact matrix multiplication applied to classification or MICMAC analysis to better understand the dependence power and driver power of those variables. The results illustrate that government policies, oil crisis, economic growth, and downturn are the most influential macro factors in photovoltaics TIS in Iran.